2017
DOI: 10.1590/1984-70332017v17n1a2
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted screening of breeding populations of an apomictic grass Cenchrus ciliaris L. segregating for the mode of reproduction

Abstract: Cenchrus ciliaris L. is an apomictic forage grass grown in pastures and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
(11 reference statements)
1
23
0
Order By: Relevance
“…Progenies of 198 hybrid plants were established for agronomic assessment and the 28 most productive plants in terms of herbage accumulation and production of leaves were selected. Cytoembryological analyses and molecular markers were used to assess the reproduction mode of the hybrids, indicating segregation for apomictic and sexual genotypes (Weiler et al 2017), also reported by Kumar et al (2010b) and Kumar et al (2017) in Cenchrus ciliaris, which reinforces the possibility of producing apomictic cultivars with desirable traits and using sexual genotypes as mother plants in future crosses. Barbosa et al (2019) established them in lines and evaluated in two physiographic regions of Rio Grande do Sul (Central Depression and Campain), showing the productive potential of some of these genotypes.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Progenies of 198 hybrid plants were established for agronomic assessment and the 28 most productive plants in terms of herbage accumulation and production of leaves were selected. Cytoembryological analyses and molecular markers were used to assess the reproduction mode of the hybrids, indicating segregation for apomictic and sexual genotypes (Weiler et al 2017), also reported by Kumar et al (2010b) and Kumar et al (2017) in Cenchrus ciliaris, which reinforces the possibility of producing apomictic cultivars with desirable traits and using sexual genotypes as mother plants in future crosses. Barbosa et al (2019) established them in lines and evaluated in two physiographic regions of Rio Grande do Sul (Central Depression and Campain), showing the productive potential of some of these genotypes.…”
Section: Introductionsupporting
confidence: 61%
“…The native germplasm is tetraploid and displays apomictic reproduction (Forbes and Burton 1961). By the apomictic reproduction mode, the seeds are clones of the mother plant (Ortiz et al 2013), which can be either a drawback or a valuable tool for crop improvement (Kumar et al 2017). Historically, the breeding of apomictic plants was limited by selection, evaluation and natural perception of the occurrence of the most vigorous and highest-yielding apomictic ecotypes (Miles 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be due to an expression of apospory in these hybrids, which was not detected by flow cytometry; therefore, a greater number of seeds should be analyzed. Several attempts have been made to develop molecular markers that can be used to discriminate between sexual and apomictic genotypes resulting from crosses in other genera, (e.g., Brachiaria, Poa, Cenchrus, and Panicum;Pessino et al, 1997;1998;Albertini et al, 2001;Dwivedi et al, 2007;Zorzatto et al, 2010;Bluma Marques et al, 2014;Worthington et al, 2016;Kumar et al, 2017). However, few reports of the use of these markers are available.…”
Section: Comparison Between Sexual and Apomictic Hybrids For Morpholomentioning
confidence: 99%
“…This approach provides very useful information from gene expression to cell metabolism and genetic linkages, and has consequently become a link among genomics, genetics, and physiology. Unlike the widely used DNA molecular markers in plant genetic research and breeding (Garrido-Cardenas et al 2017, Kumar et al 2017, proteomic polymorphisms based on 2-DE are real-time expression markers; therefore, the protein markers are beneficial for defining the relationships of molecular genetic markers with their physiological function. Furthermore, the method can generate novel insight and be useful for crop improvement.…”
Section: Introductionmentioning
confidence: 99%